Building metallurgical bonding interfaces in an immiscible Mo/Cu system by irradiation damage alloying (IDA). Issue 4 (April 2018) - Du, Jinlong; Huang, Yuan; Xiao, Chan; Liu, Yongchang
Abstract: For the immiscible Mo/Cu system with a positive heat of mixing (Δ Hm  > 0), building metallurgical bonding interfaces directly between immiscible Mo and Cu and preparing Mo/Cu laminar metal matrix composites (LMMCs) are very difficult. To solve the problem, a new alloying method for immiscible systems, which is named as irradiation damage alloying (IDA), is presented in this paper. The IDA primarily consists of three steps. Firstly, Mo is damaged by irradiation with multi-energy (186, 62 keV) Cu ion beams at a dose of 2 × 10 17  ions/cm 2 . Secondly, Cu layers are superimposed on the surfaces of the irradiation-damaged Mo to obtain Mo/Cu laminated specimens. Thirdly, the irradiation damage induces the diffusion alloying between Mo and Cu when the laminated specimens are annealed at 950 °C in a protective atmosphere. Through IDA, Mo/Cu LMMCs are prepared in this paper. The tensile tests carried out for the Mo/Cu LMMCs specimens show that the Mo/Cu interfaces constructed via IDA have high normal and shear strengths. Additionally, the microstructure of the Mo/Cu interface is characterized by High Resolution Transmission Electron Microscopy (HRTEM), X-ray diffraction (XRD) and Energy Dispersive X-ray (EDX) attached in HRTEM. The microscopic characterization results show that the expectant diffusion between Mo and Cu occurs through the irradiation damage during the process of IDA. Thus a Mo/Cu metallurgical bonding interface successfully forms. Moreover, the microscopic test results show that the Mo/Cu metallurgical interface is mainly constituted of crystalline phases with twisted and tangled lattices, and amorphous phase is not observed. Finally, based on the positron annihilation spectroscopy (PAS) and HRTEM results, the diffusion mechanism of IDA is discussed and determined to be vacancy assisted diffusion.